ANALISIS PENGARUH RASIO LIKUIDITAS, RASIO SOLVABILITAS RASIO AKTIVITAS, RASIO PROFITABILITAS, DAN RASIO PASAR TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010 â 2013) - Septiana Setianingrum, 12.05.51.0091; Irsad, Moch (Students Journal of Economic and Management, 2016)
The objective of this research is to analyse the influence of Current Ratio, Debt to Equity Ratio (DER), Total Asset Turn Over (TATO), Return On Equity (ROE), and Price Earning Ratio (PER) toward Dividen Payout Ratio (DPR) in manufacture companies that is listed in Indonesian Stock Exchange over period 2010-2013. Dividend is profit will be shared to stockholders. This study sampled using a purposive sampling and obtain data for 177 samples. This study is free from the normality test and the classical assumption test. These result indicate that Current Ratio has a positive and significant impact on DPR. Debt to Equity Ratio has a positive and significant impact on DPR. Total Asset Turn Over has a positive and but not significant impact on DPR. Return on Equity has a positive and but not significant impact on DPR. The latest results show that Price Earning Ratio has a positive and significant impact on DPR. Investor can use the result of this research as a consideration before invest.